Global perspectives on teacher motivation - Watt, Helen M. G.; Richardson, Paul W.; Smith, Kari (Current perspectives in social and behavioral sciences, 2017)
Many studies of teacher motivation have been conducted in different contexts over time. However, until fairly recently there has not been a reliable measure available to allow comparisons across samples and settings. This has resulted in an abundance of findings which cannot be directly compared or synthesised. The FIT-Choice instrument offers the opportunity to examine motivations across settings. The various studies in this book suggest that people who choose teaching as a career are motivated by a complex interaction of factors embedded within communities and cultural expectations, but seem generally to embrace a desire to undertake meaningful work that makes for a better society. Unlike some careers, where rewards are in the form of salary and status, by and large these factors are not strong drivers for people who want to become teachers. They want to work with children and adolescents, and believe they have the ability to teach